Evaluation of Liver Toxicity of 2-Methyl-3-Hydroxypyridin-4-one in Iron Overloaded Rats: Hepatotoxicity of 2-methyl-3-hydroxypyridin-4-one - Mostafavi, S. Abolfazl; Saghaie, Lotfollah; Taher, S. Masihollah; Manteghi, Naiemeh (Iranian Journal of Pharmaceutical Sciences, 2006)
Hydroxypyridinone iron chelators are currently the main candidates for development of orally active iron chelating alternatives to desferrioxamine (DFO). In the present study, the relative efficacy and liver toxicity of a bidentate chelator, 2-methyl-3-hydroxypyridin-4-one (MHPO), was studied in iron overloaded rats and compared with those of DFO. For iron overloading, rats received i.p. injections of 100 mg/kg of iron-dextran twice a week for 4 consecutive weeks. They were allowed for equilibration of iron after overloading for 15 days. Then the rats received i.p. injections of 200 mg/kg/day of either MHPO or DFO for 15 days. At the end of this period, blood samples were taken and the iron and ferritin concentrations, and the total iron binding capacity (TIBC) were determined. The activities of SGOT, SGPT and ALP were analyzed by standard colorimetric kits. Serum values for iron, TIBC and ferritin were shown to have no significant differences after the administration of either MHPO or DFO in treated rats. SGOT and SGPT values were significantly reduced after the administration of MHPO. DFO, however, was only able to reduce SGPT with the same dose. There were no significant differences between two chelators with regards to ALP. After the administration of MHPO, skin rashes were observed in a way that rats could not move. In conclusion, this study confirms that MHPO is at least as effectives as DFO at mobilizing iron, and reduces liver toxicity, however, with regard to other side effects such as its skin toxicity, further studies are required.